Do patient and proxy agree? Long-term changes in multiple sclerosis physical impact and walking ability on patient-reported outcome scales. (October 2014) - Sonder, Judith M; Balk, Lisanne J; Bosma, Libertje VAE; Polman, Chris H; Uitdehaag, Bernard MJ
Background: Patient-reported outcome scales (PROs) are useful in monitoring changes in multiple sclerosis (MS) over time. Although these scales are reliable and valid measures in longitudinal studies in MS patients, it is unknown what the impact is when obtaining longitudinal data from proxies. Objective: The objective of this paper is to compare longitudinal changes in patient and proxy responses on PROs assessing physical impact of MS and walking ability. Methods: In a prospective observational study, data on the Multiple Sclerosis Impact Scale (MSIS-29 physical) and Multiple Sclerosis Walking Scale (MSWS-12) were obtained from 137 patient-proxy couples at baseline and at two-year follow-up. Demographic and disease-related variables explaining agreement or disagreement between patients and proxies were investigated using linear regression analyses. Results: Full agreement was found in 56% (MSIS) and 62% (MSWS) of the patient-proxy couples. Complete disagreement was very rare for both scales (2% MSIS, 5% MSWS). When patients were more positive than proxies, a higher age, longer disease duration, longer patient-proxy relationship and increased levels of depression, anxiety and caregiver burden in proxies were observed. Conclusion: In the majority of the patient-proxy couples there was agreement. Proxies can serve as a valuable source of information, but caution remains essential when using scores from proxies.